The Practice of the Training on Stress Tolerance Increase of Ukrainian Students in the Sphere of Legal Education - Латковська, Тамара Анатоліївна; Латковська, Т. А.; Латковская, Тамара Анатольевна; Latkovska, Tamara A.; Сідор, Михайло Іванович; Сідор, М. І.; Сидор, Михаил Иванович; Sidor, Mykhailo I.; Голоядова, Тетяна Олексіївна; Голоядова, Т. О.; Голоядова, Татьяна Алексеевна; Holoiadova, Tetiana O.; et al. (Sciedu Press, 2019)
The new national curriculum implementation in the sphere of higher education in Ukraine raises the need for using tests as the means of students’ knowledge assessment. The authors have identified the connection both between the level of stress tolerance and between the level of test passing by means of using the correlated analysis, the Kolmogorov-Smirnov test and the T-Wilcoxon test. The level of stress tolerance has a serious impact upon the students’ test result. The students show a higher efficiency level while passing the test after visiting the training on stress tolerance increase. It has been identified that the opportunity value as to how to focus the students’ attention on the test is an important harbinger of the thesis that the education of Ukrainian students should be followed by the assessment of their psychological state. The authors have identified that the students’ psychological architype has an impact upon the education efficiency giving both similar and best results according to the results from other cultures.

Впровадження нового національного навчального плану у сфері вищої освіти в Україні викликає необхідність використання тестів як засобу оцінювання знань студентів. За допомогою кореляційного аналізу, тесту Колмогорова-Смірнова та тесту Т-Вілкоксона, автори виявили зв'язок як між рівнем стресостійкості, так і між рівнем проходження тесту. Рівень стресостійкості має серйозний вплив на результати тестування студентів. Вищий рівень працездатності студенти демонструють при проходженні тесту після відвідування тренінгу з підвищення стресостійкості. Виявлено, що значення можливості щодо того, як зосередити увагу студентів на тесті, є важливим передвісником тези про те, що навчання українських студентів має супроводжуватися оцінкою їх психологічного стану. Автори виявили, що психологічний архітип учнів впливає на ефективність навчання, дає як подібні, так і найкращі результати відповідно до результатів інших культур.
Latkovska T. The Practice of the Training on Stress Tolerance Increase of Ukrainian Students in the Sphere of Legal Education / T. Latkovska, M. Sidor, T. Goloyadova, A. Kalimbet // International Journal of Higher Education. - Vol. 8. - No. 8. - Sciedu Press, 2019. - Р. 16-23.
Keywords: education; law; testing; training; Ukraine; освіта; право; тестування; навчання; Україна; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education